Predictors of exclusive breastfeeding among infants under-six months in rural Ethiopia - Halefom Shwaye Hantal; Gebrie Melese Abite; Kassahun Animut Metkie (PLoS ONE, 2026)
Background Exclusive breastfeeding (EBF) is the practice of providing infants with only breast milk for the first six months of their life, except for medically prescribed drugs or supplements. Globally, EBF prevalence varies with low awareness in developing countries including Ethiopia. Hence, this study identified the significant predictors of the duration of EBF among infants fewer than six months in rural Ethiopia. Methods A survival analysis was used to identify the significant predictors of EBF in rural Ethiopia using the 2019 Ethiopia Mini Demographic and Health Survey (EMDHS) dataset. Results During the survey period in rural Ethiopia, a significant proportion of mothers (15.1%) do not exclusively breastfeed their infants, which still represents a major health problem. The final multivariable Weibull parametric survival model identified significant predictors of the duration of EBF in rural Ethiopia, such as, mothers with radio access (HR = 1.274, p-value 0.020), mothers delivered by C-section (HR = 0.573, p-value <0.001), mothers residing in Amhara (HR = 0.406, p-value = 0.025), Oromia (HR = 0.379, p-value = 0.017), Somali (HR = 0.112, p-value < 0.001), SNNPR (HR = 0.296, p-value = 0.002), Gambela (HR = 0.285, p-value = 0.002), Harari (HR = 0.220, p-value < 0.001), and Dire Dawa (HR = 0.234, p-value < 0.001), EIBF immediately within the first hour (HR = 1.554, p-value < 0.001), infants aged 0–1 year (HR = 0.226, p-value < 0.001), birth interval of 24 months and more (HR = 0.819, p-value = 0.034), and mothers who were currently married (HR = 0.514, p-value = 0.016). Conclusion The duration of EBF among infants less than six months in rural Ethiopia is significantly influenced by household access to radio, cesarean delivery, region, early initiation of breastfeeding, child’s age, preceding birth interval, and marital status at the 5% significance level. To improve EBF practices, there must be targeted interventions that are relevant to regions and better support for 15.1% of mothers.